1992
DOI: 10.1007/bf00318658
|View full text |Cite
|
Sign up to set email alerts
|

Plastid DNA from Pyrenomonas salina (Cryptophyceae): physical map, genes, and evolutionary implications

Abstract: Cryptomonads are thought to have arisen from a symbiotic association between a eukaryotic flagellated host and a eukaryotic algal symbiont, presumably related to red algae. As organellar DNAs have proven to be useful tools in elucidating phylogenetic relationships, the plastid (pt) DNA of the cryptomonad alga Pyrenomonas salina has been characterized in some detail. A restriction map of the circular 127 kb ptDNA from Pyrenomonas salina was established. An inverted repeat (IR) region of about 5 kb separates two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 56 publications
1
6
1
Order By: Relevance
“…The cpDNA-encoded SSU rRNAs of the cryptomonads are grouped with those of algae containing chlorophyll c or phycobiliproteins, which is also in agreement with previous trees based on SSU rRNA (29,35,37). Since the cpDNAencoded SSU rRNA of Chlorarachnion does not cluster with the cpDNA-encoded SSU rRNA of cryptomonads, the hypothesis that the two groups of algae obtained their endosymbionts independently, is further supported.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The cpDNA-encoded SSU rRNAs of the cryptomonads are grouped with those of algae containing chlorophyll c or phycobiliproteins, which is also in agreement with previous trees based on SSU rRNA (29,35,37). Since the cpDNAencoded SSU rRNA of Chlorarachnion does not cluster with the cpDNA-encoded SSU rRNA of cryptomonads, the hypothesis that the two groups of algae obtained their endosymbionts independently, is further supported.…”
Section: Resultssupporting
confidence: 76%
“…Although not supported by bootstrap analysis in the tree of Fig. 1, this relationship has been suggested previously on the basis of SSU rRNA trees (1,27,29,30). Furthermore, like the red algae, cryptomonads contain phycobilins as accessory pigments.…”
Section: Resultsmentioning
confidence: 62%
“…When the chlorarachniophyte NM is omitted from the analysis and only the cryptomonad NM is included (not shown), it forms an independent lineage, clearly separated from the green algae and land plants, which still form a very well-supported clade. However, on the basis of LSU rRNA, the red algal ancestry of the cryptomonad endosymbiont, as suggested previously (Douglas et al, 1991 ;Maier et al, 1991 ;Maerz et al, 1992 ;Van de Peer et al, 1996a) cannot be demonstrated. When only the chlorarachniophyte NM sequence is included, its phylogenetic position remains basically unchanged, but the bootstrap support for the clade formed by green algae plus land plants increases spectacularly (Fig.…”
Section: Figmentioning
confidence: 68%
“…Since the NM of cryptomonads and chlorarachniophytes still encode 18S rRNA, it could be demonstrated that the endosymbionts of chlorarachniophytes are probably related to green algae, while those of cryptomonads are most probably related to red algae ( Van de Peer et al, 1996a). Although the latter relationship is usually not supported by bootstrap analysis, it has been suggested previously on the basis of SSU rRNA (Douglas et al, 1991 ;Maier et al, 1991 ;Maerz et al, 1992). In haptophytes and heterokont algae, a remnant of the endosymbionts nucleus does not exist anymore and therefore the true nature of the endosymbiont that gave rise to their plastids can only be inferred through sequence analysis of plastid genes.…”
Section: Introductionmentioning
confidence: 72%
“…These trees suggest that the endosymbiont is most closely related to extant red algae, which is also consistent with the presence of phycobilin pigments and the site of starch storage in the endosymbionts and red algae (see McFadden, 1993, for review). In addition, phylogenetic trees inferred from sequences of plastid genes such as rbcL and 16S rRNA also suggest that the endosymbiont could share a common ancestry with red algae (Douglas et al, 1991a, Douglas & Turner 1991Maerz et al, 1992).…”
Section: Introductionmentioning
confidence: 99%